Effect of Application of Selective UV-absorbers/antioxidants on Raw and Bleached Jute Fabrics by Pad-batch-dry Process for Reduction of Its Photo-degradation and Photo-yellowing Character. Issue 15 (23rd November 2022) - Samanta, A. K.; Singhee, Deepali
ABSTRACT: To reduce photo-fading of jute, raw and H2 O2 bleached jute fabrics have been treated with selective UV-absorbers and antioxidant compounds by pad-batch-dry technique and subjected to photo-exposure in a weather-o-meter for different hours (0–320 h). The corresponding changes in tensile strength and the rate of reduction in whiteness index and rate of increase in yellowness index with consequent changes in K/S value have been evaluated. Among the selected UV-absorbers and antioxidants, sodium azide and LTDP offer good stability against photo-fading, but these treatments are not fast to washing. On the other hand, 1% benztriazole treatment gives medium to good level of resistance against photo-yellowing with reasonable wash fastness. Two percent benztriazole is applied on jute fabric by the pad-batch-dry technique in acidic media (with acetic acid) shows higher stabilization of whiteness retention (i.e. lesser extent of photo-yellowing) under UV-light exposure than other UV-absorbers/antioxidants though is associated with some small loss in tensile strength. The mechanism of possible interaction between benztriazole and major jute constituents has also been established by comparing the reaction with similar model compound (benzaldehyde) in place of reaction between jute–-hemi-cellulose–CHO and benztriazole. UV–VIS spectrophotometric and FTIR analysis undertaken made to support the said reaction mechanism.